Maqâṣid al-Qur'ân dan Deradikalisasi Penafsiran dalam Konteks Keindonesiaan - Ulya Fikriyati (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2014)
This article deals with the viewpoint that the reading of the Qur'ân by a certain generation is subject to criticism by the following generation. The article seeks to offer, as an example, the deradicalization of interpreting the so-called ?radical? verses of the Qur'ân in Indonesian context. Islam in Indonesia always interact with various races, ethnicities, religions and beliefs, and therefore requires a type of exegesis different from other regions such as the Middle East. For the radicalization of interpretation, this article offers what is called the maqâṣid al-Qur'ân as its parameter. The maqaṣid al-Qur'ân consists of seven points: 1) Hifz al-dîn wa tatwîr wasâilih, 2) Hifz al-nafs wa tatwîruh?, 3) Hifz al-``aql wa tatwîruh, 4) Hifz al-mâl wa tanmîyat was?ilih, 5) Hifz al-ird wa tatwîr al-wasâil li al-husûl alayh, 6) Taḥqîq al-ḥuqûq al-insânîyah wa mâ yandarij tahtahû, 7) Hifz al-??lam wa ?im?ratuh?. As spirit and parameter, the maqâsid al-Qur'ân necessitates the dialectics of dynamic interpretation without any judgment of infidelity or heresy. If a certain reading of the Qurânic verses deviates from these seven maqâsid al-Qur'ân above, it deserves to be examined further, but not to be immediately suppressed.